2018
DOI: 10.1007/s12195-018-0525-z
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Microelectrode Arrays for Electrical and Optical Measurements of Human Stem Cell-Derived Cardiomyocytes

Abstract: Associate Editor William E. Bentley oversaw the review of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 47 publications
3
50
0
Order By: Relevance
“…As proof-of-principle and to demonstrate the robustness of our technique, we demonstrated that MEAs with silk-passivated interconnects could record signals both from cultured cells (HL-1) as well as primary tissues (brain, heart). Significantly, in the case of HL-1 cells we recorded signals with signal-to-noise >78, which compares favorably other devices recently used to study cardiac monolayers, including graphene MEAs with SU8 passivation 7 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As proof-of-principle and to demonstrate the robustness of our technique, we demonstrated that MEAs with silk-passivated interconnects could record signals both from cultured cells (HL-1) as well as primary tissues (brain, heart). Significantly, in the case of HL-1 cells we recorded signals with signal-to-noise >78, which compares favorably other devices recently used to study cardiac monolayers, including graphene MEAs with SU8 passivation 7 .…”
Section: Discussionmentioning
confidence: 61%
“…Examples of bioelectronic devices include multi-electrode arrays (MEAs) and field-effect transistors (FETs) which have been interfaced with neuron or cardiac cells for multiplexed, realtime readouts of electrophysiological activity 4 , while other classes of devices have achieved ondemand drug delivery, localized stimulation, power generation and chemical sensing capabilities 5,6 . Advances in nanoscience have played a key role in each of these areas by enabling cellular-scale, noninvasive devices such as transparent graphene MEAs 7 and freestanding nanowire arrays 8,9 that could access the cytosol for intracellular measurements.…”
mentioning
confidence: 99%
“…Moreover, transparent and biocompatible indium tin oxide (ITO) and graphene‐based MEAs were fabricated to achieve the simultaneous optical and electrical recordings. [ 42–44 ] Interestingly, conductive hydrogel micropillars were applied to MEAs fabrication, showing improved signal amplitude and SNR. [ 45 ] Recently, an electrical shell‐like recording device that wrapped around the cell in 3D was reported to improve the cell–electrode coupling.…”
Section: Electrophysiology Detectionmentioning
confidence: 99%
“…To characterize the impedance of the electrodes before and after PEDOT:PSS electrodeposition, electrochemical impedance spectroscopy (EIS) was performed in a threeelectrode electrochemical cell using a potentiostat (Gamry R600+, Gamry Instruments). 17…”
Section: Electrochemical Characterization Of Microelectrodesmentioning
confidence: 99%